2014
DOI: 10.5603/ep.2014.0012
|View full text |Cite
|
Sign up to set email alerts
|

Kontrola glikemii i jej zmienność głównymi czynnikami ryzyka mikroalbuminurii u dzieci chorych na cukrzycę typu 1

Abstract: Introduction: To assess in a prospective study the course and the predictors of microalbuminuria in children and adolescents with type 1 diabetes. Material and methods: 438 children and adolescents who developed diabetes in the years 1985-2004 were followed for 9.2 ± 3.4 years from the diagnosis. Microalbuminuria was assessed on the basis of timed overnight urine collections performed once per year. Variability of glycated haemoglobin was expressed as a coefficient of variation (%) calculated by dividing stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Long-term variability in HbA 1c has been proposed as an important risk factor related to mortality [3][4][5][6], cardiovascular disease (CVD) [7][8][9], nephropathy [10][11][12] and other complications [13][14][15][16][17] independent of HbA 1c levels. Recently, there has been considerable interest in the emerging association between glycaemic variability and decline in cognitive function [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term variability in HbA 1c has been proposed as an important risk factor related to mortality [3][4][5][6], cardiovascular disease (CVD) [7][8][9], nephropathy [10][11][12] and other complications [13][14][15][16][17] independent of HbA 1c levels. Recently, there has been considerable interest in the emerging association between glycaemic variability and decline in cognitive function [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also demonstrated that MAU is also a powerful predictor of CVD in both diabetic and non-diabetic subjects [ 6 , 7 ]. MAU is usually absent at diagnosis but may develop in children with type 1 diabetes and poorer metabolic control [ 8 ]. On the other hand, intensive control of blood glucose level can prevent the onset and progression of MAU [ 9 ], and the incidence of decreased estimated glomerular filtration rate (eGFR) was rare in diabetic patients without preceding MAU [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…If we compare our results to other studies on HbA 1c variability, there have been three that have studied only DR development [ 13 , 15 , 16 ], three that have studied only nephropathy [ 11 , 12 , 14 ], and one that has studied both forms of microangiopathy [ 10 ]. The most important study was by Herman et al [ 15 ], a retrospective study focusing on the CV-HbA 1c of over 35,891 T1DM patients.…”
Section: Discussionmentioning
confidence: 97%
“…The first study is by Marcoveccchio et al [ 12 ], who found that 438 patients from a sample of 1232 patients with DM1 had a positive relationship between SD-HbA 1c and MA with HR 1.04, and also a positive relationship between SD-HbA 1c and MA with HR 1.31. The second study was by Nazim et al [ 14 ], a cross-sectional study that also found a positive relationship between MA and SD-HbA 1c (HR 1.04), and a third study by Waden et al [ 11 ], a prospective 5.7-year follow-up of 2107 T1DM patients again found a positive relationship between SD-HbA 1c and a progression in renal status (HR 1.92).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation